Contactless measurements of photocarrier transport properties in perovskite single crystals - Xiwen Gong (Nature Portfolio, 2019)
Reliable and consistent measurement of the carrier diffusion length in metal halide perovskite single crystals has proven difficult. Here Gong, Huang et al. systematically included very dilute quantum dot quenchers into perovskite crystals and develop a contactless and self-consistent method for the task.